Clustering Data Penjualan Toko XYZ Menggunakan Metode K-Means - Margaretta, Putri; Sari, Betha Nurina; Ridha, Azhari Ali (Peneliti.net, 2024)
Sales, A Process Involving Sellers Offering Goods Or Services To Buyers With The Objective Of Profiting From The Transaction, Is A Pivotal Activity In Business. Xyz Store, A Micro, Small, And Medium Enterprise (Msme) Specializing In Children’s Clothing Sales, Has Been Operational Since 2009. Transactions Can Be Conducted Online, Enabling Buyers To Shop Without The Need To Visit The Physical Store. However, Xyz Store Faces A Challenge In Stock Management, Specifically The Mismatch Between Demand And Product Availability, Leading To An Accumulation Of Less Popular Items. By Understanding Sales Trends, Xyz Store Can Optimize Their Stock Management, Either By Curtailing The Purchase Of Stocks For Less Sold Items Or By Substituting Less Popular Items With New Ones That May Be More Appealing To Potential Buyers. Through The Evaluation Stage In The Kdd Method, It Was Determined That The Optimal Number Of Clusters In This Study Is Three, With An Evaluation Result Of 0.5063460425226173. These Three Clusters Were Identified As Less Popular Items, Moderately Popular Items, And Very Popular Items. Cluster 1, Deemed Less Popular, Comprises 84 Items. Cluster 2, Which Is Moderately Popular, Includes 12 Items. Meanwhile, Cluster 3, Identified As Very Popular, Contains Only 4 Items. This Study Provides Valuable Insights Into Sales Strategies And Stock Management At Xyz Store For Enhancing Efficiency And Sales.